THE PLACE OF INNOVATION MANAGEMENT IN THE LIFE OF ECONOMIC ENTITIES - CSŐSZ CSONGOR (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The innovation management -changing the way organizations work- plays a crucial role in the sustainability and competitiveness of economic entities. This paper explores the place of innovation management within organizations through a comprehensive literature review, examining its definition, evolution, and drivers. The utility of innovation management is discussed in terms of improving organizational agility, enhancing employee engagement, and reducing costs. The paper also identifies key targets of innovation management, including organizational structures, leadership practices, and work processes. Finally, the reasons why organizations should pursue innovation management are explored, highlighting the need to adapt to technological change, address shifting workforce dynamics, and respond to globalization. By embracing innovation management, organizations can foster a culture of adaptability and creativity, ensuring long-term growth and competitive advantage.